MODERN METHODS OF TEACHING FOREIGN LANGUAGES. IN THE CASE OF ENGLISH (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article highlights several ways to learn English effectively and some of the modern learning technologies in language learning as well.